Acceptability and satisfaction of project MOVE: A pragmatic feasibility trial aimed at increasing physical activity in female breast cancer survivors. Issue 4 (1st March 2018) - Pullen, Tanya; Sharp, Paul; Bottorff, Joan L.; Sabiston, Catherine M.; Campbell, Kristin L.; Ellard, Susan L.; Gotay, Carolyn; Fitzpatrick, Kayla; Caperchione, Cristina M.
Abstract: Objective: Despite the physical and psychological health benefits associated with physical activity (PA) for breast cancer (BC) survivors, up to 70% of female BC survivors are not meeting minimum recommended PA guidelines. The objective of this study was to evaluate acceptability and satisfaction with Project MOVE, an innovative approach to increase PA among BC survivors through the combination of microgrants and financial incentives. Methods: A mixed‐methods design was used. Participants were BC survivors and support individuals with a mean age of 58.5 years. At 6‐month follow‐up, participants completed a program evaluation questionnaire ( n = 72) and participated in focus groups ( n = 52) to explore their experience with Project MOVE. Results: Participants reported that they were satisfied with Project MOVE (86.6%) and that the program was appropriate for BC survivors (96.3%). Four main themes emerged from focus groups: (1) acceptability and satisfaction of Project MOVE, detailing the value of the model in developing tailored group‐base PA programs; (2) the importance of Project MOVE leaders, highlighting the value of a leader that was organized and a good communicator; (3) breaking down barriers with Project MOVE, describing how the program helped to address common BC related barriers; and (4) motivation to MOVE, outlining how the microgrants enabled survivors to be active, while the financial incentive motivated them to increase and maintain their PA. Conclusion: The findings provide support for the acceptability of Project MOVE as a strategy for increasing PA among BC survivors.